Advanced Introduction to Platform Economics, Robin Mansell and W. Edward Steinmueller (2020). (1st June 2021) - Flew, Terry
Review of: Advanced Introduction to Platform Economics, Robin Mansell and W. Edward Steinmueller (2020)Cheltenham: Edward Elgar Publishing, 176 pp., ISBN 978-1-78990-062-0, p/bk, £15.95